Problems of legal regulation of digital transformation of agriculture of the Republic of Kazakhstan - Kuandykova, E.S.; Baideldinov, D.L.; Hoffmann, T. (Акад. Е.А. Бөкетов ат. Қарағанды ун-ті КЕАҚ баспасы, 2023)
In the context of the best world practices the study is an overview of the legal regulation of the process of digital transformation of public administration of agriculture in the Republic of Kazakhstan. The hypotheses of this study are based on the analysis of the legal nature of the world practice of digital transformation of economic development and international cooperation of modern states. The research revealed that agriculture is a branch of the economy that is particularly in need of the introduction of information and communication technologies and, consequently, the improvement of legal regulation of the activities of public administration in the digital reality. The analysis of state programs and national projects of the Republic of Kazakhstan provides grounds for concluding that the digitalization of the Kazakh economy in agriculture is a priority. The dependence of the effectiveness of digital solutions in the agro-industrial complex on the level of public administration organization is substantiated: digitalization resources contribute to a more focused and resultoriented public policy through the use of legal monitoring capabilities. Digitalization is a rapidly growing trend in agriculture, when it does not just replace analog technologies traditionally used in practice, but develops new development options for effective solutions to problems in the industry, among which the introduction of legal mechanisms is of paramount importance. The study contains an analysis of the development of the legal foundations of digitalization in the industry, taking into account the problems at all levels of the process – from the issues of providing agricultural producers with an elementary level of Internet access to increasing the level of legal regulation of state management in the field of digitalization management.
Қазақстан Республикасындағы ауылшаруашылығын цифрлық трансмормациялауды құқықтық реттеудің мәселелері
Проблемы правового регулирования цифровой трансформации сельского хозяйства Республики Казахстан
Keywords: digitalization; agriculture; public administration; legal regulation; information and communication technologies; modernization